Kinetics of CO2 absorption into a novel 1‐diethylamino‐2‐propanol solvent using stopped‐flow technique. Issue 10 (25th June 2014) - Liu, Helei; Liang, Zhiwu; Sema, Teerawat; Rongwong, Wichitpan; Li, Chen; Na, Yanqing; Idem, Raphael; Tontiwachwuthikul, Paitoon; Idem, Raphael; Tontiwachwuthikul, Paitoon
<x xml:space="preserve">Abstract</x> A stopped‐flow apparatus was used to measure the kinetics of carbon dioxide (CO2) absorption into aqueous solution of 1‐diethylamino‐2‐propanol (1DEA2P) in terms of observed pseudo‐first‐order rate constant (ko) and second‐order reaction rate constant (k2), in this work. The experiments were conducted over a 1DEA2P concentration range of 120–751 mol/m3, and a temperature range of 298–313 K. As 1DEA2P is a tertiary amine, the base‐catalyzed hydration mechanism was, then, applied to correlate the experimental CO2 absorption rate constants obtained from stopped‐flow apparatus. In addition, the pKa of 1DEA2P was experimentally measured over a temperature range of 278–333 K. The Brønsted relationship between reaction rate constant (obtained from stopped‐flow apparatus) and pKa was, then, studied. The results showed that the correlation based on the Brønsted relationship performed very well for predicting the absorption rate constant with an absolute average deviation of 5.2%, which is in an acceptable range of less than 10%. © 2014 American Institute of Chemical Engineers AIChE J, 60: 3502–3510, 2014